2010
DOI: 10.3109/00016341003801706
|View full text |Cite
|
Sign up to set email alerts
|

Maternal weight and body composition in the first trimester of pregnancy

Abstract: Contrary to previous reports, mean maternal weight and mean body composition values remain unchanged in the first trimester of pregnancy. This has implications for guidelines on maternal weight gain during pregnancy. We also recommend that calculation of BMI in pregnancy and gestational weight gain should be based on accurate early pregnancy measurements, and not on self-reported or prepregnancy measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 39 publications
2
98
0
1
Order By: Relevance
“…It was observed that the mother's average weight, BMI and body composition parameters were unchanged during early pregnancy, indicating that changes had begun after the first quarter [22]. In our study, we observed a significant increase in the mean values of body composition in multigravidae when compared to primigravidae.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was observed that the mother's average weight, BMI and body composition parameters were unchanged during early pregnancy, indicating that changes had begun after the first quarter [22]. In our study, we observed a significant increase in the mean values of body composition in multigravidae when compared to primigravidae.…”
Section: Discussionsupporting
confidence: 64%
“…A longitudinal study followed 170 pregnant women and observed elevation in body weight, total body water (TBW), extracellular water (ECW) and intracellular water (ICW), confirming that the fat deposition and the increased fluid retention appear to be responsible for gestational weight gain [20]. When comparing primigravidae and multigravidae by the segmental BIA method in the first trimester, it was observed that the mother's average weight, the BMI and the parameters of body composition remain unchanged during early pregnancy, indicating that these changes should start after the first quarter [22].…”
Section: Introductionmentioning
confidence: 96%
“…Maternal weight, used in calculating BMI, was measured at the first visit to the maternal welfare clinic. If the mother had her first clinic visit after the 10th week of pregnancy, her weight for the 10th week was estimated based on the difference between her weight at the first and last maternal clinic visit assuming linear weight gain during the second and third trimesters of pregnancy (28,29) . Information on paternal weight and height was not collected from fathers of the 6-year-olds.…”
Section: Participantsmentioning
confidence: 99%
“…If mother had her first clinic visit after the 10th week of pregnancy, weight at week 10 was estimated based on the difference between weight at the first and last maternal welfare clinic visit and assuming linear weight gain during the second and third trimesters of pregnancy (28,29) . --Weight and height information was not collected from the fathers of 6-year-old children.…”
Section: Finnish Children Healthy Eating Index (Fchei)mentioning
confidence: 99%
“…A Scottish study found that the prevalence of obesity had increased from 9.4% to 18.9% over a 12 year period (Kanagalingam et al, 2005). In other studies in Britain and Ireland, nearly a fifth of women booking for antenatal care were obese (Fattah et al, 2010;CMACE 2010). The severity of obesity is also increasing.…”
Section: Rising Obesity Levels and Rising Caesarean Section Ratesmentioning
confidence: 99%